Effect of 6-Week Instrument-Assisted Soft Tissue Mobilization on Joint Flexibility and Musculotendinous Properties - Naoki Ikeda; Kazuya Hiratsuka; Tadao Isaka (MDPI AG, 2024)
Instrument-assisted soft tissue mobilization (IASTM) stimulates soft subcutaneous tissues by applying pressure to the skin with a specialized bar or spurtle-like instrument. No studies have verified whether several weeks of continuous IASTM alone can alter joint flexibility and musculotendinous properties in healthy participants. We examined the effect of a 6-week IASTM program on joint flexibility and the musculotendinous properties of the lower limbs. Fourteen healthy men (aged 19-35 years) who participated in a 6-week IASTM program (3 days weekly) for the soft tissue of the posterior aspect of one lower leg were included. The other leg served as the control. Before and after the intervention, we measured the maximal ankle joint dorsiflexion angle (dorsiflexion range of motion: DFROM) and maximal passive torque (MPT), a measure of stretch tolerance. We measured muscle and tendon stiffness using shear wave elastography on the gastrocnemius and Achilles tendon. IASTM significantly increased the DFROM and MPT (p < 0.05 for both). However, no significant changes were observed in muscle and tendon stiffness. None of the parameters changed significantly in the control group. The 6-week IASTM program increased stretch tolerance and joint flexibility but did not change muscle and tendon stiffness.